The Effect of Using Instagram as Media Towards Students’ Writing Descriptive Text - Mhd. Dendi Musandra; Lusi Marleni (Journal of Innovative and Creativity, 2021)
This experimental research was conducted at tenth grade of SMAN 2 Kuok. This research aims to find out whether there is an effect on using Instagram as media towards the students’ writing descriptive text, in academic year 2019/2020. This is a quasi-experiment research. From the entire population, two classes were chosen as the sample. Class X IIS as the experiment class and class X MIPA as the control class. The experimental class was taught by using Instagram as media meanwhile control was taught by using Google Classroom as media. The data were obtained by using Pre-test and Post-test. Pre-test was given to both classes before the treatment and Post-test of both classes were analyzed by using t-test. Based on the data analysis of the research showed that the average students post-test in experimental class were 70, and control class has average students post-test were 67. It means there is a significant difference in the students’ writing skill between the students who were taught by using Instagram and those who were taught using teacher method. It can be conclude that there was effectivenes of using Instagram as media toward the students’ writing skill at the tenth grade of SMAN 2 Kuok.